Studi Sistem hukum Indonesia - Prof.Dr.H.Faried Ali, S.H., Ms., Anwar Sulaiman,S.H., M.H. (PT Refika Aditama, 2012)
menunjukan kompetensi bidang ilmu ilmu sosial dan ilmu politik dalam payung pancasila